Path Analysis: Implementation of Information Motivation Behavioral Skill Model on Tertiary Preventive Behavior in Type II Diabetes Melitus - Aktif Cahyaning Tyas; Bhisma Murti; Didik Gunawan Tamtomo (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia. Hyperglycemia over a long period of time increases the occurrence of complications. Complications due to type 2 DM can be prevented or delayed by implementing tertiary preventive behavior. This study aims to analyze the influence of the Information Motivation and Behavior Skill Model on tertiary preventive behavior in type 2 DM patients. Subjects and Method: This research with a cross-sectional design was conducted in Boyolali Regency, Central Java from November to December 2023. The research was conducted at 25 posbindu in Ngemplak and Nogosari Districts. The sample size was 200 adults with a diagnosis of type 2 DM who were selected using the stratified random sampling method. The dependent variable is tertiary preventive behavior. The independent variables are information, motivation, behavioral skills, age, gender, education, and employment. Data collection was carried out using questionnaire interviews. Data were analyzed using path analysis in the STATA 13 application. Results: There is a positive relationship between behavioral skills and tertiary preventive behavior (b= 0.16; 95% CI= 0.02 to 0.29; p= 0.023). There is a positive relationship between information and behavioral skills (b= 0.25; 95% CI= 0.13 to 0.38; p<0.001). There is a positive relationship between motivation and behavioral skills (b= 0.38; 95% CI= 0.15 to 0.41; p<0.001). The path analysis model has good model suitability, as indicated by the following suitability indicators: p= 0.244; RMSEA= 0.045; CFI= 0.98; TLI= 0.95; SRMR= 0.032. Conclusion: Tertiary preventive behavior in adult type 2 DM patients is directly influenced by behavioral skills. Tertiary preventive behavior is indirectly influenced by information and motivation. Tertiary preventive behavior in type 2 DM patients increases with good information, strong motivation and good behavioral skills.